Schitt's Creek. The complete third season [videorecording (DVD)] - Levy, Eugene, 1946-; Levy, Daniel, 1983- (Schitt's Creek (Television program), 2017)
The Rose family's dreams of escaping their town are suddenly thwarted when the town's potential buyer succumbs to a diabetic coma. It's now clear that their stay in this simple setting will be much longer than they ever imagined. Faced with this horrific truth, the Roses must do the only thing they can: change the town from within. Contains thirteen episodes and bonus features.